Risk of Pneumonitis and Outcomes After Mediastinal Proton Therapy for Relapsed/Refractory Lymphoma: A PTCOG and PCG Collaboration - Tseng, Yolanda D; Hoppe, Bradford S; Dedeckova, Katerina; Patel, Chirayu G; Hill-Kayser, Christine E; Miller, David M; Maity, Amit; Mendenhall, Nancy P; Mailhot Vega, Raymond B; Yock, Torunn I; Baliga, Sujith; Hess, Clayton B; et al. (International journal of radiation oncology, biology, physics, 2021)
PURPOSE: Despite high response rates, there has been reluctance to use radiation therapy for patients with relapsed/refractory (r/r) Hodgkin (HL) or aggressive non-Hodgkin lymphoma (NHL) given concerns for subacute and late toxicities. Symptomatic pneumonitis, a subacute toxicity, has an incidence of 17% to 24% (≥grade 2) even with intensity modulated radiation therapy. Proton therapy (PT), which has no exit radiation dose, is associated with a lower dose to lung compared with other radiation techniques. As risk of radiation pneumonitis is associated with lung dose, we evaluated whether pneumonitis rates are lower with PT. METHODS AND MATERIALS: Within an international, multi-institutional cohort, we retrospectively evaluated the incidence and grade of radiation pneumonitis (National Cancer Institute Common Terminology Criteria for Adverse Events v4) among patients with r/r HL or NHL treated with PT. RESULTS: A total of 85 patients with r/r lymphoma (66% HL, 34% NHL; 46% primary chemorefractory) received thoracic PT from 2009 to 2017 in the consolidation (45%) or salvage (54%) setting. Median dose was 36 Gy(RBE). Before PT, patients underwent a median of 1 salvage systemic therapy (range, 0-4); 40% received PT within 4 months of transplant. With a median follow-up of 26.3 months among living patients, 11 patients developed symptomatic (grade 2) pneumonitis (12.8%). No grade 3 or higher pneumonitis was observed. Dose to lung, including mean lung dose, lung V5, and V20, significantly predicted risk of symptomatic pneumonitis, but not receipt of brentuximab, history of bleomycin toxicity, sex, or peritransplant radiation. CONCLUSIONS: PT for relapsed/refractory lymphoma was associated with favorable rates of pneumonitis compared with historical controls. We confirm that among patients treated with PT, pneumonitis risk is associated with mean lung and lung V20 dose. These findings highlight how advancements in radiation delivery may improve the therapeutic ratio for patients with relapsed/refractory lymphoma. PT may be considered as a treatment modality for patients with relapsed/refractory lymphoma in the consolidation or salvage setting.
Keywords: lymfom; recidiva; Humans; lidé středního věku; dítě; Child; Female; rizikové faktory; mladý dospělý; dospělí; Aged; výsledek terapie; senioři; lidé; Lymphoma; mladiství; Radiation Pneumonitis; Adult; ženské pohlaví; Male; Middle Aged; radiační pneumonitida; Adolescent; Mediastinum; Treatment Outcome; Proton Therapy; Recurrence; Young Adult; mužské pohlaví; protonová terapie; Risk Factors; mediastinum